1985
DOI: 10.1128/aac.28.3.461
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of Ro 15-8074, a new oral cephalosporin, against Neisseria gonorrhoeae

Abstract: Ro 15-8074, a new cephalosporin the pivaloyloxymethylester of which (Ro 15-8015) is orally absorbable, showed greater in vitro activity than cefaclor ngainst 48 Neisseria gonorrhoeae strains, including 25 penicillinase-producing strains. Unlike cefaclor, Ro 15-8074 was unaffected by increase in ihoculum size, and it exhibited a remarkable stability against gonococcal P-lactamase hydrolysis.The emergence of penicillinase-producing Neisseria gonorrhoeae (PPNG) strains showing high resistance to penicillin has pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
6
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 9 publications
(8 reference statements)
2
6
0
Order By: Relevance
“…The compounds were much more active than cefaclor or cephalexin against H. influenzae and N. gonorrhoeae and inhibited beta-lactamase-producing isolates of these species. Our results are similar to those of Ng et al (5) against N. gonorrhoeae.…”
Section: Resultssupporting
confidence: 82%
“…The compounds were much more active than cefaclor or cephalexin against H. influenzae and N. gonorrhoeae and inhibited beta-lactamase-producing isolates of these species. Our results are similar to those of Ng et al (5) against N. gonorrhoeae.…”
Section: Resultssupporting
confidence: 82%
“…Studies reported elsewhere showed Ro 15-8074 to be very active against H. influenzae and Neisseria gonorrhoeae, including P-lactanmase-producing strains (7,9,10,13 …”
mentioning
confidence: 99%
“…The 7'-substitutions provide for an increased Ro 15-8074 antimicrobial activity against the Enterobacteriaceae, Haemophilus influenzae, and Neisseria spp. compared with currently available orally administered cephalosporins (2,7,(9)(10)(11)). An additional feature of Ro 15-8074 is its P-lactamase stability (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other workers have found that Ro 15-8074/001 is more active than cefaclor, cefadroxil, ampicillin, and TMP-SMX against the Enterobacteriaceae (2) and more active than amoxicillin-clavulanic acid and cefaclor against pencillinase-producing and nonpenicillinaseproducing Neisseria gonorrhoeae (1). Further studies are indicated to determine the clinical efficacy of this new oral cephalosporin.…”
mentioning
confidence: 99%